(untitled) (Indian Journal of Animal Production and Management, 2018)
Present experiment was conducted to assess the effect of anaerobic biodegradation on change in nutrient composition of brewers’ dried grain (BDG). In 4 X 3 factorial experiment BDG was inoculated with rumen liquor filtrate at the rate of 0, 10, 20 and 40% on volume/ weight basis. of BDG: inoculum for 3 different durations of 2, 4 and 6 days to assess the change in nutrient compositios Which resulted in significant (p≤ 0.05) increase in crude protein content from 24.72±0.35 to 34.30±0.35% and significant (p≤ 0.05) decrease in crude fiber content from 26.03±0.36 to 14.41±0.36%.